2020
DOI: 10.1080/10691898.2019.1704201
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Engagement in an Introductory Statistics Course

Abstract: This article presents the results of a case study from one professor's experience teaching an introductory statistics course. The goal of this study was to better understand student perceptions of engagement in a statistics course. Voluntary, self-reported data were collected daily for students to evaluate the engagement level of the class that day, and students also identified activities that they considered engaging. A final survey was administered at the end of the semester to provide a holistic, retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
(4 reference statements)
1
7
0
1
Order By: Relevance
“…This lack of STEM identity may contribute to barriers to learning computation-related skills (Berndt et al, 2021;Esnard et al, 2021). For example, their low sense of belonging/identity in computing (Chew and Dillon, 2014;Davies et al, 2015;Lawton and Taylor, 2020) may result in attentional biases (Okon-Singer, 2018;Cui et al, 2019) that further lower their engagement and motivation (Lawton and Taylor, 2020) and prohibit them from moving on to the next level (Davies et al, 2015). Additionally, these challenges have been identified among the under-resourced, marginalized under-represented minoritized (URM) population in STEM (Lisberg and Woods, 2018;Singer et al, 2020).…”
Section: Preparing Students To Enter the Css Curriculummentioning
confidence: 99%
“…This lack of STEM identity may contribute to barriers to learning computation-related skills (Berndt et al, 2021;Esnard et al, 2021). For example, their low sense of belonging/identity in computing (Chew and Dillon, 2014;Davies et al, 2015;Lawton and Taylor, 2020) may result in attentional biases (Okon-Singer, 2018;Cui et al, 2019) that further lower their engagement and motivation (Lawton and Taylor, 2020) and prohibit them from moving on to the next level (Davies et al, 2015). Additionally, these challenges have been identified among the under-resourced, marginalized under-represented minoritized (URM) population in STEM (Lisberg and Woods, 2018;Singer et al, 2020).…”
Section: Preparing Students To Enter the Css Curriculummentioning
confidence: 99%
“…The researchers discovered that, although the mean changes in the subscale scores were greater in the first half of the semester, the majority of individual student scores varied in both halves of the semester. Lawton and Taylor (2020) took an even closer look at when the student attitudes change by asking how engaging the class was at the end of each class. Although their self-designed attitude scale can't be compared directly to the SATS-36, they found that (a) the most drastic changes occurred near the beginning and end of the course, and (b) the instructor consistently rated classes as more engaging than the average student.…”
Section: Current Landscape Of Attitudes Toward Statisticsmentioning
confidence: 99%
“…Many recent studies [29][30][31][32][33][34][35] show that implementing a project-based view either for an entire statistics course, a module in a course or as an assessment tool can result in the improvement of student engagement and admittedly make them learn more compared to traditional education. Students seemed to favour projects to be included in statistics because they could learn better in such an environment that simulated future work and could obtain skills that are valued at the labour market as well.…”
Section: Project-based Learningmentioning
confidence: 99%